O-Health-Edu: Advancing oral health: A vision for dental education. (30th September 2020) - Tubert-Jeannin, S; Field, J; Davies, J; Manzanares, C; Dixon, J; Vital, S; Paganelli, C; Quinn, B; Gerber, G; Akota, I
Abstract: The prevalence and burden of untreated oral diseases throughout the life course remains high worldwide, and inequalities in oral health and dental care are increasing. This is a major public health issue that is not being enough addressed by the health care systems. To better manage populations' oral health, oral health professionals must be trained to adapt to population needs and societal and technological changes. Furthermore, dental institutions must fulfill their social responsibility by prioritizing educational and research activities that promote advancing individual and community health. In Europe, great variability exists between dental programs within the same country or between countries. This variability is an issue as European graduates can practice around the European Union through mutual recognition of their qualifications. This might lead to inequities in the availability, accessibility, acceptability and quality of health services. The convergence of competencies and quality standards at the international level must thus be better clearly identified, defined and improved. The purpose of the O-Health-Edu, EU funded project, "Advancing Oral Health: A vision for Dental Education" is thus to assess the current situation concerning the oral health professionals' education (OHP) and to identify educational priorities so that future graduating OHPs have competencies aligned with emerging population needs. The project is supported within the KA203 - "Cooperation for Innovation and the Exchange of Good Practices - Strategic Partnerships for higher education" Erasmus program. It began in October 2019 for three years, with eight European university partners and the ADEE (Association for Dental Education in Europe). The firsts steps consist of a scoping review to identify the available information followed by a questionnaire survey to gather more comprehensive data so that to build an opened data source, and a glossary of dental education terms. Key messages: Few Information about the current situation of dental education in Europe. Graduates must be equipped with adequate competencies to face populations needs.